Manajemen Rekrutmen Tenaga Pendidik dalam Peningkatan Mutu Sekolah Dasar Islam Swasta di Samarinda - Anisa Nur Lail; Rahmat Soe’oed; Usfandi Haryaka (Departement of Mathematics Education, 2023)
This study aims to determine the planning, implementation, supervision, constraints, and solutions in managing teacher recruitment in improving the quality of private Islamic elementary schools in Samarinda. A qualitative approach using the case study method was used to collect data from principal informants, vice principals, and teaching staff. Methods of data collection using interview techniques and document study. The collected data were analyzed interactively and tested the validity of the data was using source triangulation. The results of this study indicate that planning for the recruitment of teaching staff is carried out by determining the qualifications applicants must possess. The recruitment of teaching staff is carried out internally and externally. At the supervisory level, school principals and foundation leaders carry out teacher recruitment activities to monitor teacher recruitment activities by participating in the teacher recruitment process. Recruitment management constraints are applicants with personalities that do not match the predetermined qualifications and do not pass the selection process.